Counter-hegemony of gender stereotypes through film: Critical discourse analysis in Barbie Movie (2023) - Mardhika, Herdiantyara; Agustin, Sari Monik (Universitas Bunda Mulia, 2025)
Gender ideology, which refers to gender roles has been constructed and separated the roles of men and women using the terms femininity and masculinity. This ideology is believed by society and then forms a hegemony. Hegemony is also spread through popular film culture. Often, films perpetuate gender inequality and portray women as marginal figures under male domination. However, the phenomenon of hegemony gives rise to an oppositional force known as Organic Intellectuals. These organic intellectuals frequently resist existing domination through films. This research aims to investigate how counter-hegemony is depicted in Barbie (2023). Employing a critical paradigm, a qualitative approach, and critical discourse analysis, this study dissects the text in the film by examining the subject-object position and the audience's position in Barbie (2023). The analysis reveals that the film, Barbie (2023) illustrates the hegemony depicted by the opposing actors, similar to films in general. However, resistance is evident in the film, with the director, also functioning as an organic intellectual, expressing feminist ideas. This portrayal acts as a counter to the hegemony of gender stereotypes in Barbie (2023).